CHANGES IN THE ENVIRONMENTAL FEATURES OF PULICAT LAKE IN RELATION TO TIDES - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
The present observations were undertaken to gain knowledge on therange of variations in some of the important hydrobiological parameters in relationto tidal rhythm, as a part of the investigation on the ecology of thePulicat lake. Information available on the tidal cycles in some of the Indianestuaries is mainly due to the works of Rangarajan (1958), George and Kartha(1963), Qasim and Gopinathan (1969), Dehadrai (1970b), Sarma and Ganapati(1970) and Dehadrai and Bhargava (1972). But nothing is known aboutthis important aspect of the ecology of the Pulicat lake.